Methylation analysis of Gasdermin E shows great promise as a biomarker for colorectal cancer. (16th April 2019) - Ibrahim, Joe; Op de Beeck, Ken; Fransen, Erik; Croes, Lieselot; Beyens, Matthias; Suls, Arvid; Vanden Berghe, Wim; Peeters, Marc; Van Camp, Guy
Abstract: In addition to its implication in hereditary hearing loss, the Gasdermin E ( GSDME ) gene is also a tumor suppressor involved in cancer progression through programmed cell death. GSDME epigenetic silencing through methylation has been shown in some cancer types, but studies are yet to fully explore its diagnostic/prognostic potential in colorectal cancer on a large‐scale. We used public data from The Cancer Genome Atlas (TCGA) to investigate differences in GSDME methylation and expression between colorectal cancer and normal colorectal tissue, and between left‐ and right‐sided colorectal cancers in 432 samples. We also explored GSDME 's diagnostic capacity as a biomarker for colorectal cancer. We observed differential methylation in all 22 GSDME CpGs between tumor and normal tissues, and in 18 CpGs between the left‐ and right‐sided groups. In the cancer tissue, putative promoter probes were hypermethylated and gene body probes were hypomethylated, while this pattern was inversed in normal tissues. Both putative promoter and gene body CpGs correlated well together but formed distinct methylation patterns with the putative promoter exhibiting the most pronounced methylation differences between tumor and normal tissues. Clinicopathological parameters, excluding age, did not show any effect on CpG methylation. Although the methylation of 5 distinct probes was a good predictor of gene expression, we could not identify an association between GSDME methylation and expression in general. Survival analysis showed no association between GSDME methylation and expression on 5‐year patient survival. Through logistic regression, we identified a combination of 2 CpGs, that can discriminate between cancer and normal tissue with high accuracy (AUC = 0.95) irrespective of age and tumor stage. We also validated our model in 3 external methylation datasets, from the Gene Expression Omnibus database, and similar results were reached. Our results suggest that GSDME is a promising biomarker for the detection of colorectal cancer. Abstract : Aberrant Gasdermin E ( GSDME ) methylation in cancer makes it a candidate biomarker gene. This is the first study to thoroughly analyze GSDME methylation in the largest colorectal adenocarcinoma patient cohort to date (N = 432) using publicly available data. We identified a combination of CpGs, that can discriminate between colorectal cancer and normal tissue samples with high accuracy (AUC = 0.95). Additionally, we found significant differences in GSDME methylation between left‐ and right‐sided colorectal cancers.